Analisis Implementasi Kaidah Kebahasaan dalam Promosi Pendidikan pada Infografik Kemendikbud di Sosial Media Instagram - Aden Wildan Baihaqi; Laylur Rohman; Celsia Aurora Tania Putri; Hendri Bastian (Jurnal Ilmiah Wahana Pendidikan, 2023)
The research aims to determine 1) the implementation of language rules in educational promotion on the Ministry of Education and Culture (Kemendikbud) infographics on Instagram social media; and 2) the effectiveness of implementing language rules in educational promotion on the Ministry of Education and Culture (Kemendikbud) infographics on Instagram social media. The research method employed in this study is observation, which involves direct observation of the research object. The conclusions of this study are as follows: 1) The implementation of language rules in educational promotion on the Ministry of Education and Culture (Kemendikbud) infographics on Instagram social media has been properly and correctly applied according to the rules of the Indonesian language; 2) The implementation of language rules in educational promotion on the Ministry of Education and Culture (Kemendikbud) infographics on Instagram social media has been proven effective as it adheres to the language rules stipulated in PUEBI (Indonesian Spelling and Language Usage Guidelines) and is easily understood.